Pembelajaran Kitab Al-Miftah Lil Ulum Dalam Meningkatkan Kemampuan Membaca Kitab Kuning Di Pondok Pesantren Ulum Karang Tanjung Kebumen - Azizah, Alfiyah Nur; Chamidi, Agus Salim; Faisal, Faisal (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
Implementation of learning the book Al-Miftah Lil Ulum in improving the ability to read the book at the Raudlotul Ulum Islamic boarding school Karang Tanjung Kebumen. The purpose og this research is: (1) describes how the stages of planning learning the book Al-Miftah Lil Ulum in improving the ability to read the yellow book in female students of Islamic boarding schools Raudlotul Ulum Kebumen. (2) explanation of how the stages of implementing the study of the book Al-Miftah Lil Ulum in improving the ability to read the yellow book for female students of Islamic bosrding schools Raudlotul Ulum kebumen. This research is a descriptive qualitative research. The data collected analyzed and interpreted in a concise andclear form so that it is easy to understand and conclude. Data collection techniques carried out by researchers, namely by using observation, interviews, and documentation. As for research dubjects to obtain data or facts in research namely: (1) lurah of Islamic boardig school, (2) ustadzah of Islamic boarding school, (3) students of Islamic boardig school. Based on the results of research on the implementation of the book of Al-Miftah Lil Ulum learning in improving reading skills the yellow book at the Raudlotul Ulum Islamic boarding school karang tanjung as follows: (1) how to implement the learning of the implementation of learning the book Al-Miftah Lil Ulum namely opening, appreciation, delivery of material, understanding of evaluation material, understanding of evaluation material and clasing (2) obstacles in learning the book Al-Miftah Lil Ulum at the Raudlotul Ulum Islamic boarding school in Kebumen. Reseachers found that there were two inhibiting factors, namely internal factors, and external factors. Internal factors, namely motivation, interests, and different characteristics of stundents, external factors, namely family, parental attention